2021
DOI: 10.1016/j.idcr.2021.e01260
|View full text |Cite
|
Sign up to set email alerts
|

An enemy in shadows—Mycoplasma hominis septic arthritis and iliopsoas abscess: Case report and review of the literature

Abstract: Highlights The pathogenic potential of Mycoplasma hominis. The diagnostic challenges of M. hominis extragenital infections. M. hominis septic arthritis, particularly in immunocompromised hosts needs to be considered. Molecular methods have revolutionized the detection of M. hominis and can prevent devastating consequences. Prolonged antibiotic therapy targeting M. hominis in addition to appropriate surgical interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Mainly, six Mycoplasma species (M. pneumoniae, M. genitalium, Ureaplasma (U) urealyticum, U. parvum, M. hominis, M. penetrans) have been demonstrated to cause human illness (Waites et al, 2005), such as acute respiratory disease (Waites et al, 2017), joint infections (Ali et al, 2021a;Maȓginean et al, 2021), genital and urinary tract infections (Peter et al, 2018), and neurological disturbance (D'Alonzo et al, 2018;He et al, 2021a). On the other hand, some species mainly infecting animals like M. suis, M. ovis, and M. haemofelis have been detected in humans and regarded as zoonotic pathogens (Maggi et al, 2013b).…”
Section: Human Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mainly, six Mycoplasma species (M. pneumoniae, M. genitalium, Ureaplasma (U) urealyticum, U. parvum, M. hominis, M. penetrans) have been demonstrated to cause human illness (Waites et al, 2005), such as acute respiratory disease (Waites et al, 2017), joint infections (Ali et al, 2021a;Maȓginean et al, 2021), genital and urinary tract infections (Peter et al, 2018), and neurological disturbance (D'Alonzo et al, 2018;He et al, 2021a). On the other hand, some species mainly infecting animals like M. suis, M. ovis, and M. haemofelis have been detected in humans and regarded as zoonotic pathogens (Maggi et al, 2013b).…”
Section: Human Infectionmentioning
confidence: 99%
“…Clinically, arthritis associated with M. pneumoniae infection has been diagnosed in children (Azumagawa et al, 2008). In addition, septic arthritis caused by M. hominis (Ali et al, 2021a) as well as U. parvum (MacKenzie et al, 2010) has been reported in immunosuppressed patients. M. hominis has been identified as a novel periprosthetic joint infection (a rare postoperative complication) using a new tool called "metagenomic sequencing" (Wang et al, 2021a).…”
Section: Mycoplasma Infection and Urogenital Diseasesmentioning
confidence: 99%
“…Since then, a variety of M. hominis genital infections have been reported 11. Besides, it has been implicated in prosthetic and periprosthetic osteoarticular infection,13–15 retroperitoneal and pelvic abscesses,9 16–18 endocarditis,19 septic arthritis,20 postsurgical meningitis,21 brain abscess22 and ventriculitis 23…”
Section: Discussionmentioning
confidence: 99%